Study Of Liquid Organic Fertilizer Tech Nano In The Rate Of Increase In Growth Beginning Cuttings Bagal Plant Cane Ps-881 (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2017)
The purpose of this study to determine the effect of the concentration of liquid organic fertilizer Plus the best in the rate of increase in the initial growth of sugarcane cuttings. Based on the research results, it can be concluded as follows: 1). There is a significant effect of the concentration of POC Plus to the increased growth of cuttings of sugarcane in all parameters of observations studied, include: the speed of germination, the length of plants, number of leaves, root length, number of roots, fresh weight per plant and dry weight per plant during germination of plants cane. 2). The best value is achieved by treatment P6 Plus POC at 6 ml per liter of water for treatment had no significant with P7 on all parameters studied observation, especially in dry weight per plant.Â Keynote : Liquid Organic Fertilizer, Technology NanoÂ